México hacia una sociedad del conocimiento - Héctor Carreón Mendoza; Ricardo Melgoza Ramos (Nóesis)
It's important for Mexico to become a knowledge society with a clear strategy in its development plan regarding the investment on transfer technology, the increment of intellectual capital, a greater linking of the entities that generate scientific advancements, the establishment of public policies that encourage science and technology innovation, and the protection of intellectual property.